PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA MELALUI MODEL KOOPERATIF TIPE THINK PAIR AND SHARE (TPS) - Patmanidar Patmanidar (Dharmas Education Journal (DE_Journal), 2021)
This research is based on the low learning outcomes of class V SD Negeri 161 / VIII Sidorukun Kec. Rimbo Ulu Kab. Tebo, where many students have not reached KKM 75. The low student learning outcomes are because many students are still less active in the learning process. This study aims at improving student learning outcomes in the classroom using the Think Pair Share 3 (TPS) type of cooperative learning model. This type of research was classroom action research (PTK). The research subjects were grade V SD Negeri 161 / VIII Sidorukun Kec. Rimbo Ulu Kab. Tebo, with 18 students. The design of this research was the model of Kemmis and Taggart (planning, implementing, observing, reflecting). Qualitative data analysis techniques were in the form of observation sheets, while quantitative data are learning outcomes obtained from tests. This research has succeeded in improving student learning outcomes in simple aircraft material. In cycle I classical student learning completeness was 44.4% with an average value of 72.8, then an increase in cycle II was 94.4% with an average value of 83.4, an increase that occurred from cycle I to cycle II. is equal to 50. So it can be concluded that the Think Pair Share (TPS) type of cooperative learning model can improve the process and improve student science learning outcomes on simple aircraft material.